Anti-Money Laundering and Combating the Financing of Terrorism : Niger - World Bank (GIABA and the World Bank, Washington, DC, 2013)
The assessment of the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) regime in Niger was conducted on the basis of the Forty Recommendations and the Nine Special Recommendations on the financing of terrorism drawn up in 2003 and 2001, respectively, by the Financial Action Task Force (FATF), and on the AML/CFT Methodology of 2004. The assessment was based on the laws, regulations, and other materials supplied by the national authorities of Niger, as well as the information gathered in the course of the country visit from June 16 to 27, 2008. During its visit, the assessment team met with the managers and representatives of all the relevant government agencies and the private sector The assessment was conducted by an evaluation team from the World Bank and the Intergovernmental Anti-Money Laundering Group in West Africa (GIABA). To this end, they analyzed the institutional framework, the AML/CFT laws and regulations, regulations, guidelines and other obligations, as well as regulatory or other regimes in force in Niger for combating money laundering and the financing of terrorism. The capacity, implementation, and effectiveness of all these mechanisms were assessed as well. This report provides a summary of the AML/CFT measures in force in Niger as at the date of the on-site visit or immediately thereafter. It describes and analyzes those measures, and makes recommendations on how certain aspects of the system could be strengthened. It also sets out Niger s level of compliance with the FATF 40+9 Recommendations.